# trig

posted by .

TRIG Identities, Gr. 12:
Prove:
cot4x=1-tan^2x/2tan2x

• trig -

just apply the double-angle formula for tan(2x) and take the reciprocal

• trig -

okay, thank you, would that still apply if it was cot4x=1-tan^2(2x)/2tan2x? because ive got the right side for this one but the cot4x is throwing me off, how would you solve that side?

• trig -

you are exactly right

tan(4x) = 2tan2x/(1-tan^2(2x))
so, cot(4x) is the reciprocal, as needed.

## Similar Questions

1. ### Trigonometry

Use the trig Identities to find the other 5 trig functions. Problem 7.)Tan(90-x)=-3/8 8.)Csc x=-13/5 9.)Cot x=square root of 3 10.)Sin(90-x)=-.4563 11.)Sec(-x)=4 12.)Cos x=-.2351 I need HELP!
2. ### Math- gr.12 Trig.

Hi, could someone explain to me how to use a counterexample in trig to prove whether something is either an identity or equation?
3. ### Math

Prove Trig. Identities 1. sec è (sec è - cos è)= tan^2 è 2. tan^2 è (1 + cot^2 è) = sec^2 è
4. ### trig

please help me. use trig. identities to find the exact value. tan 25° + tan 5° / 1- tan 25° tan 5°
5. ### trig

please help me. use trig. identities to find the exact value. tan 25° + tan 5° / 1- tan 25° tan 5°
6. ### Trig

Use Trig identities to verify that sec^4(x)-tan^4(x)=1+2tan^2(x), Only work with one side of the equation
7. ### TRIG..............

Q.1 Prove the following identities:- (i) tan^3x/1+tan^2x + cot^3x/1+cot^2 = 1-2sin^x cos^x/sinx cosx (ii) (1+cotx+tanx)(sinx-cosx)/sec^3x-cosec^3x = sin^2xcos^2x.
8. ### Trig Identities

Proving identities: 1) 1+ 1/tan^2x = 1/sin^2x 2) 2sin^2 x-1 = sin^2x - cos^2x 3) 1/cosx - cosx = sin x tan x 4) sin x + tan x =tan x (1+cos x) 5) 1/1-sin^2x= 1+tan^2 x How in the world do I prove this...please help... I appreciateyour …
9. ### Math-Trigonometry

Show that if A, B, and C are the angles of an acute triangle, then tan A + tan B + tan C = tan A tan B tan C. I tried drawing perpendiculars and stuff but it doesn't seem to work?
10. ### Trig Identities

Prove the following identities: 13. tan(x) + sec(x) = (cos(x)) / (1-sin(x)) *Sorry for any confusing parenthesis.* My work: I simplified the left side to a. ((sinx) / (cosx)) + (1 / cosx) , then b. (sinx + 1) / cosx = (cos(x)) / (1-sin(x)) …

More Similar Questions